Congenital perineal grove: an unusual Anorectal anomaly in females—report of two cases and literature review - Dilawar, Bakhtawar; Khan, Amala; Shahzadi Dilawar; Zafar Nazir (Journal of the Pakistan Medical Association, 2023)
Congenital perineal grove (CPG) is a rare anorectal anomaly; only 65 cases have been reported in literature. Two cases who were referred for evaluation of a lesion in the perineum are reported here. The patients were diagnosed clinically as CPG in neonatal period and were initially managed conservatively. Surgery was required in one case as the lesion was persistent and symptomatic. A high index of suspicion is required for diagnosis of CPG to avoid parental anxiety and unnecessary diagnostic work-up and surgery. Surgery is required only in cases where the lesion persists or there is infection, pain, and ulceration. Keywords: Anorectal malformations, Perineal cleft, Perineal grove.